2019
DOI: 10.1016/j.vas.2019.100070
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial evaluating the effect of bandaging on the healing of sole ulcers in dairy cattle

Abstract: Highlights Sole ulcer (SU) is a common claw disease in dairy cattle, where the effect of bandaging is still questionable. Non-bandaged SU were more likely to heal than bandaged SU. Wound size of SU had a significant effect on locomotion, whereas bandaging had no effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Studies that have assessed the healing rate of sole lesions following different treatment protocols monitored lesion outcomes at multiple timepoints ( Lischer et al, 2002a ; Thomas et al, 2015 ; Klawitter et al, 2019 ). We recognize that this would be a more robust approach to judge the recovery of sole lesions than a single follow-up assessment, but our priority was to use our available resources to maximize the number of enrolled animals and allow the estimation of genetic parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have assessed the healing rate of sole lesions following different treatment protocols monitored lesion outcomes at multiple timepoints ( Lischer et al, 2002a ; Thomas et al, 2015 ; Klawitter et al, 2019 ). We recognize that this would be a more robust approach to judge the recovery of sole lesions than a single follow-up assessment, but our priority was to use our available resources to maximize the number of enrolled animals and allow the estimation of genetic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment success can be determined by visual assessment of lesion healing or the resolution of visible lameness; both are reported to have similar time frames. Approximately 60 to 70% of uncomplicated sole ulcers were covered in a layer of new horn after 4 wk ( Van Amstel et al, 2003 ; Klawitter et al, 2019 ). With prompt and effective treatment, more than 75% of cows with sole lesions were no longer lame after 35 d ( Thomas et al, 2015 ), although this was only true for 15% of cows that were chronically lame when treated ( Thomas et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Klawitter et al [ 63 ] reported that the use of topical treatment and applying a bandage to M2 digital dermatitis lesions for four weeks, changing the bandage on a weekly basis, increased the cure rate compared to lesions that only received the topical treatment. In contrast, a recent study reported that sole ulcers were less likely to heal following treatment when a bandage was applied [ 64 ]. However, a bandage may be beneficial for severe cases when the corium is considerably exposed or when the lesion is excessively bleeding [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…This means the bandage should be applied correctly and changed at least in 3 days or preferably earlier, especially if it gets wet (Shearer et al, 2015). In a study by Klawitter et al (2019) sole ulcers healed faster when only therapeutic trim, wooden claw block and iodine ointment were used and no bandage was applied. When the bandage is applied to protect claw lesion that are almost completely healed, it may exceptionally be removed after 5 days, given it stays dry.…”
Section: Therapeutic Approach To Claw Horn Lesionsmentioning
confidence: 99%